EDUCATIONAL OPPORTUNITY WISATAWAN DALAM MELAKUKAN PERJALANAN WISATA DAN PENGARUHNYA TERHADAP TINGKAT PENGETAHUAN DAN KEPUASAN WISATAWAN DI SUMATERA BARAT - Sarbaitinil Sarbaitinil; I Wayan Thariqy Kawakibi Pristiwasa (Universitas Merdeka Malang, 2018)
This study aims to find out how big educational tourist opportunities in travel and its influence on the level of knowledge and satisfaction of tourists in West Sumatra. This study uses quantitative descriptive research method with reference to the concept of educational oppurtunity and the level of satisfaction to tourists. Population in this research is social situation that is government, stakeholder, society and tourists. The instrument in this study is a questionnaire distributed to tourists visiting the province of West Sumatra through the area of ​​cultural tourism in 2016, interview guides and observations, using Coding model, interpretation and congrulation. Research results indicate that: (1) Tourists visiting West Sumatera have the opportunity to learn the cultural uniqueness, it's just that tourists have not felt the level of satisfaction of tourism in West Sumatra. This is caused by the obstacles that exist in tourist sites for example, the ability of the community to serve tourists well, the ability of public communication is limited to tourists. Thus, the educational opportunity of tourists who travel is classified as psychological satisfaction. The satisfaction of tourists is more seen from the supporting facilities and tourist attractions (2) educational opportunity that significant tourists with the satisfaction of tourists in West Sumatra Fhit of 5.189 with a value of significance = 0.007. The value is small from 0.05. Educational opportunity is an information for tourists in a travel tour to fit the level of customer satisfaction.